Forests of symbols world, text & self in Malcolm Lowry's fiction - McCarthy, Patrick A. 1945- (Univ. of Georgia Press, 1994)
Malcolm Lowry's reputation as a novelist rests primarily on the masterpiece Under the Volcano. Lowry is also well known for what he did not write; that is, for his anguished inability to complete his works. Under the Volcano is one of only two novels published in Lowry's lifetime; the bulk of his writings were still in various stages of composition when he died in 1957. In Forests of Symbols, Patrick A. McCarthy addresses the central enigma of the writer's life: his dependence on writing for his sense of identity and his fear that the process of composition would leave him with no identity apart from his work. Reading across Lowry's corpus - complete and incomplete, published and unpublished - McCarthy looks not only at the ways in which acts of reading, writing, and interpretation define Lowry's characters but also the threat they pose to those characters' sense of a coherent identity
Keywords: Lowry, Malcolm <1909-1957> - Critique et interprétation; Lowry, Malcolm <1909-1957> -- Criticism and interpretation; Lowry, Malcolm -- 1909-1957; Moi (Psychologie) dans la littérature; Symbolisme dans la littérature; Psychological fiction, English -- History and criticism; Self in literature; Symbolism in literature; Identität